The Student Loan Market is Broken: Preempting State Law Would Make it Worse - Frotman, Seth (Administrative & Regulatory Law News, 2019)
[...]the Higher Education Act defines a range of additional federal protections that should alleviate the burden of this unprecedented and untenable debt, including programs like Public Service Loan Forgiveness (PSLF) and interest-rate caps for certain military borrowers. [...]ED specifically advises borrowers to reach out to their servicer if they are experiencing financial hardship or other repayment obstacles. [...]TILA's implementing regulations required a creditor, for each transaction, to disclose its identity, certain financing and payment information, annual and variable percentage rates, and other specified information. Because these types of disclosures significantly overlapped with the disclosure requirements under the HEA, Congress exempted lenders and servicers from TILA so that they would not be subject to duplicative requirements. [...]when the Congress amended HEA to include 1098g, TILA permitted states and creditors to apply to the Federal Reserve Board for a determination of whether a state law disclosure is "substantially the same in meaning as disclosure required under this subchapter."